Validation of the Chinese version of the Somatic Symptom Scale-8 in patients from tertiary hospitals in China - Li, Tao; Wei, Jing; Fritzsche, Kurt; Toussaint, Anne C.; Zhang, Lan; Zhang, Yaoyin; Chen, Hua; Wu, Heng; Ma, Xiquan; Li, Wentian; Ren, Jie; Lu, Wei; et al. (Frontiers in Psychiatry, 2022)
Objective: To validate the Chinese language version of the Somatic Symptom Scale-8 (SSS-8) in a sample of outpatients attending tertiary hospitals in China. Methods: A Chinese language version of the SSS-8 was completed by outpatients (n=699) from psychosomatic medicine, gastroenterology/neurology, and traditional Chinese medicine clinics of nine tertiary hospitals between September 2016 and January 2018. The reliability of this version was tested. The Patient Health Questionnaire-15 (PHQ-15), the Somatic Symptom Disorder–B Criteria Scale (SSD-12), the Patient Health Questionnaire-9 (PHQ-9), the General Anxiety Disorder-7 (GAD-7) scale, the Medical Outcome Study 12-item Short Form Health Survey (SF-12) and the World Health Organization Disability Assessment Schedule (WHO DAS 2.0) were rated to test construct validity. The criterion validity was tested by using the Semi-structured Clinical Interview for DSM-5 (Research Version) (SCID-5-RV) for somatic symptom disorder (SSD) as the diagnostic gold standard to explore the optimal cutoff score of the SSS-8. Results: The average age of the recruited participants was 43.08 (±14.47). 61.4% of them were female. The internal consistency derived from the sample was acceptable (Cronbach α =.78). Confirmatory factor analyses resulted in the replication of a three-factor model (cardiopulmonary symptoms, pain symptoms, gastrointestinal and fatigue symptoms) (comparative fit index = 0.95, Tucker-Lewis index = 0.92, root mean square error of approximation = 0.10, 90% confidence interval = 0.08–0.12). The SSS-8 sum score was highly associated with PHQ-15 (r = 0.74, p <.001), SSD-12 (r = 0.64, p <.001), GAD-7 (r = 0.59, p < 0.001), and PHQ-9 (r = 0.69, p < 0.001). The patients with more severe symptoms showed worse quality of life and disability The optimal cutoff score of SSS-8 was 9 (sensitivity=0.67, specificity=0.68). Conclusions: Our preliminary assessment suggests that the Chinese language version of the SSS-8 has reliability and validity sufficient to warrant testing further in research and clinical settings.